2022
DOI: 10.1590/1516-3180.2021.0757.r1.20122021
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to physical activity among adults in primary healthcare units in the National Health System: a cross-sectional study in Brazil

Abstract: BACKGROUND: Many factors may negatively impact physical activity (PA), but studies lack evidence of individual predictors of perceived barriers to PA among adults in primary healthcare units. OBJECTIVE: To analyze associations between sociodemographic characteristics, health conditions, leisure-time physical activity (LTPA), PA counseling and perceived barriers to LTPA among adult patients in primary healthcare units of the National Health System in Brazil. DESIGN AND SETTING: Cross-sectional study on a repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“… 35 However, lack of time is reported as one of the top five barriers to decreasing PA among several populations in Africa, North America, Asia, and South America. 47 51 Thus, women are at high risk of declining their quality of life due to reduced PA levels. For instance, in California, 143 Latin women aged 40–79 indicated that time constraints prevented them from increasing their PA levels.…”
Section: Discussionmentioning
confidence: 99%
“… 35 However, lack of time is reported as one of the top five barriers to decreasing PA among several populations in Africa, North America, Asia, and South America. 47 51 Thus, women are at high risk of declining their quality of life due to reduced PA levels. For instance, in California, 143 Latin women aged 40–79 indicated that time constraints prevented them from increasing their PA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Other barriers include lack of social support, low self-confidence, and limited access to facilities and resources. These factors, combined with cultural and traditional barriers, may contribute to lower levels of physical activity among women in Saudi Arabia [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…A mulher realiza muitas tarefas no seu dia a dia, tendo ela filhos ou não. Dessa forma, o cansaço e a falta de tempo são as principais barreiras para a prática de atividades físicas (SOUZA, SANTOS et al, 2022). Como consequência, muitas mulheres são inativas ou não realizam pelo menos 150 minutos de atividade física por semana e assim, não se beneficiam da sua prática regular.…”
Section: Introductionunclassified